Emotional Responses to Suffering in the Testament of Job - Mermelstein, Ari (AJS review, 2025)
In spotlighting Job's reputation as a patient sufferer, the Testament of Job pays close attention to the negative emotions that Job successfully stifles and their association with power. Job's interlocutors contend that suffering renders one utterly powerless, and the fact that Job's emotions do not reflect his powerlessness is thus irrational. Their conception of power, which focuses on Satan's domination and Job's own reduced capacities, yields a set of "feeling rules" that demand specific emotional responses to suffering. Job objects to this perspective because it focuses exclusively on power dynamics in the material world. His conception of power produces different feeling rules: because Job's suffering restores agency, it should not provoke emotional excess in him. The author devotes significant attention to emotion in order to address the fundamental question raised by Job's predicament: Can suffering be an opportunity for empowerment? The Testament of Job is thus an ideal case study for examining the relationship between emotion and power.